Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan di PT. Telkom Akses Bandung - Dian Dania Apriyanti; Nurul Try Oktaviyanti; Dian Candra Fatihah (Universitas Batanghari Jambi, 2022)
This study have purpose to understand the influence of leadership style on employee performance at PT. Telkom Akses Bandung. The research method that we used is quantitative descriptive method, which we do by using a questionnaire and a literature survey. The sample taken in this study were 32 respondents using purposive sampling technique. The main data of this study came from a questionnaire survey measured by a likert scale and SPSS 24 was used for statistical processing. The data analysis method used is a simple linear regression method and the correlation method between variables. Based on the result of the study, the correlation coefficient between leadership style and employee performance was 0,497, which means it has a relationship level on the medium category. Furthermore, the results of the hypothesis T test indicate that there is an influence between leadership style on employee performance, namely the hypotesis is accepted because the t value > t table (3.318 > 2.045). the value of the determination coefficient is 25%, which means that leadership style affects employee performance by 25% and the remaining 75% is influenced by other factors or variables that didn’t examined by the author. The problem encountered is the indicator of leadership style, namely the firmness of the leader in fostering informal relationships with his subordinates, which still has to be improved, resulting in teh work of subordinates being less focused. The writer’s suggestion for PT. Telkom Akses Bandung, namely the company periodically conducts leadership training for all elements of the leadership so that coordination and communication relations with subordiantes can run even better so as to improve employee performance as expected.